The Effect of Peer Assisted Learning on Medical Students' Learning in a Limbs Anatomy Course - Sahar Almasi Turk; Ali Mousavizadeh; Amrollah Roozbehi (Tabriz University of Medical Sciences, 2015)
Introduction: Peer assisted learning (PAL) is the expansion of knowledge and abilities through active assistance and guidance among groups of people who are not trained teachers, but still assist and support one another's learning. The aim of this study was evaluation of PAL in teaching skills and learning limb anatomy for medical students. Methods: In this quasi-experimental study, students entering Yasuj University of Medical Sciences (YUMS) in academic year 2012-13 were allocated to two equal groups of 28 participants, with PAL as the intervention group and conventional teaching methods as the comparison group at the beginning of the fourth week of the course. The course content for the PAL group was divided into seven roughly equal parts, the duties of students were determined and the time table was the same for two groups. Formative exams from each topic and summative exams about upper and lower limb anatomy were given. Abilities and skills of peer teachers were assessed by a researcher-made questionnaire through peer assessment. Data was analyzed using a paired t-test. Results: The mean scores of the PAL intervention group showed a significant statistical increase on seven out of ninth formative exams in relation to the comparison group (P<0.05). The mean differences (confidence interval) of the nine formative exams were (-.25, -1.98, 1.48), (-.59, -1.66, 1.43), (-1.75, -3.46, -.04), (-1.99, -3.14, -.86), (-1.61, -1.98, -1.48), (-2.04, -3.66, -.43), (-1.75, -3.46, -.039), (-1.89, -3.14, -.93) and (-1.62, -2.84, -.41), respectively. Scores on both summative exams in the PAL group indicated statistically significant differences compared to those of the comparison group (P<0.05). Mean differences and CI of multiple choice, naming pictures and short answer questions of the midterm exam were (-1.46, -2.52, -.4), (-1.52, -2.2, -.01) and (-1.1, -2.57, -.42), respectively, and for the final exam they were (-1.21, -2.59, -.4), (-1.68, -2.65, -.47) and (-1.09, -2.2, -.01), respectively. Descriptive statistics showed that the abilities and skills of peer teachers in gradually improved in the majority of areas improved. Conclusion: The mean scores of PAL group were higher than those of the comparison group. Since learning in this method occurs through debate and discussion and acquisition of skills and communication grew in students, it could be an accountable approach.